Kulturowa rola uniwersytetu w kontekście kryzysu państwa dobrobytu - Kościelniak, Cezary (Człowiek i Społeczeństwo, 2014)
The paper analyses how the changes of the welfare state meets the transformation of the higher education policy in the cultural perspective. Culture plays an important role in building the concept and practice of the Western welfare state institution, also the knowledge institutions. The idea of the contemporary university is suitable to the welfare expectations. On the one hand, the universities are expected to provide mass education and minimize the differences between social strata’s. On the other, after 50 years of the welfare regime in Western Europe, the state of the art universities and departments did not expand their accessibility to the students from lower social classes. What is more, in some cases, the access to is more difficult than before. The next part of the paper includes analyses of the Polish exception of the welfare state, based on the concept of the “post-grange culture” and its application to the higher education policy.